PENGARUH KUALITAS PENETAPAN PAJAK, PEMERIKSAAN PAJAK, SURAT TEGURAN, DAN SURAT PAKSA TERHADAP PENCAIRAN TUNGGAKAN PAJAK (Studi di Kantor Pelayanan Pajak Pratama Pekanbaru Tampan Riau Tahun 2012-2013) - Meilia Rochmawati; Zirman -; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of tax assessment, tax audit, warning letter, and the letter forced to liquefaction tax arrears. The population in this study are corporate taxpayers registered in the tax office pratama pekanbaru riau totaling 2,735 corporate taxpayers. The samples are corporate taxpayers who have tax arrears during the years 2012-2013 which totaled 648 corporate taxpayers. This study using purposive sampling method as sampling is sampling in accordance with the purpose. Data analysis method used in this study is multiple regression. The results showed that the quality of the assessment. Known t (1.577) <t table (2.365) and significant (0.159)> 0.05. Tax audits are known t (0.187) <t table (2.365) and significant (0.857)> 0.05. A letter of reprimand is known t (2.380)> t table (2.365) and significant (0,049) <0.05. Forced known letter t (2.434)> t table (2.365) and significant (0.045) <0.05. R2 value that is equal to 99.2%, which means that the independent variable in this study could affect the dependent variable. While the remaining 0.8%, which means influenced by variables were included in this study.Keywords: quality of tax assessment, tax audit, a letter of reprimand, forced letter, and liquefaction tax arrears.